2015
DOI: 10.1177/0956797615595607
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Social Biases in People With Autism

Abstract: Implicit social biases are ubiquitous and are known to influence social behavior. A core diagnostic criterion of Autism Spectrum Disorder (ASD) is abnormal social behavior. Here we investigated the extent to which individuals with ASD might show a specific attenuation of implicit social biases, using the Implicit Association Test (IAT) across Social (gender, race) and Nonsocial (flowers/insect, shoes) categories. High-functioning adults with ASD showed intact but reduced IAT effects relative to healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…(2010) report that autistic participants are more resistant to this mistake, though they are not more explicitly aware of the conjunction rule. Along similar lines, Birmingham et. al.…”
Section: Social Stereotypessupporting
confidence: 56%
“…(2010) report that autistic participants are more resistant to this mistake, though they are not more explicitly aware of the conjunction rule. Along similar lines, Birmingham et. al.…”
Section: Social Stereotypessupporting
confidence: 56%
“…Yet, individuals with ASD struggled to align the conceptualizations of their communicative signals with those of their interaction partners when the problem space afforded multiple solutions. This impairment could be isolated because the novel communicative setting prevented access to pre-existing contextual cues that cognitively-able individuals with ASD can capitalize on to resolve ambiguity (Au-Yeung, Kaakinen, Liversedge, & Benson, 2015;Birmingham, Stanley, Nair, & Adolphs, 2015;Branigan, Tosi, & Gillespie-Smith, 2016;Brewer, Biotti, Bird, & Cook, 2017;Hahn, Snedeker, & Rabagliati, 2015;Nadig, Seth, & Sasson, 2015;Pijnacker, Hagoort, Buitelaar, Teunisse, & Geurts, 2009) . Under these experimentally-generated conditions, built to recreate the fleeting ambiguities of everyday interaction, communication requires more than pruning a decision tree of possible signals or iteratively optimizing behavioral outcomes (Botvinick & Weinstein, 2014;Donoso, Collins, & Koechlin, 2014;Keysers & Perrett, 2004) .…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have shown that moral cognition is based on conscious and unconscious processes22, the corresponding conscious and unconscious processes involved in social convention remain unclear. Decision-making processes based on social conventional rules have been shown to involve one or more of three possible components: Trait inferences based on characteristics23, inferences based on behaviours24, and evaluation of outcomes as outputs25. Typically developing individuals in early adolescence make trait inferences as well as behaviour- and intention-based inferences26.…”
mentioning
confidence: 99%
“…Individuals with ASD evidence deficits in more complex intention-based moral judgement tasks that require integration of information about agent mental states with information about the outcomes of behaviours19. Recent studies using IAT (implicit association test) tasks have shown that implicit social biases are largely intact in ASD23, suggesting that individuals with ASD do have the ability to make trait inferences. Children with ASD can also make behaviour-based inferences.…”
mentioning
confidence: 99%